Targeting HOXA in engineered iPSCs and pre-clinical leukaemia models - Abuhantash, Mays (2023)
Haematopoiesis is a highly regulated process governed by a complex network of transcription factors and signalling molecules. HOXA genes are master regulators of embryonic development and haematopoiesis. In normal haematopoiesis, expression of HOXA is high in haematopoietic stem and progenitor cells (HSPCs) and decreases upon differentiation and maturation. Aberrant expression of the HOXA cluster, particularly HOXA9, is associated with malignant haematopoiesis.